2013
DOI: 10.1002/prep.201300065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ADN/GAP‐Based and ADN/Desmophen®‐Based Propellant Formulations and Comparison with AP Analogues

Abstract: Several ADN-based rocket propellant formulations containing different pre-polymers (GAP diol/triol, Desmophen® 2200), curing agents (BPS, Desmodur® N100, Desmodur® N3400), plasticizers (BDNPA-F, TMETN), and filler types (Al, HMX) have been manufactured. Propellant formulations were characterized by tensile tests, SEM analyses and DMA measurements. The study has focused on characterizations of the propellants in terms of evaluation of the strength and strain capability, investigation of the presence/absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The use of polyfunctional alkynes as alternative, isocyanate‐free curing agents for GAP binder systems is by now well‐established, at least at the laboratory scale 4–8, 10, 13, 14, 1618. Although a variety of such agents have been developed, the most comprehensibly explored ones have been bispropargyl succinate (BPS) 4–8, 14, 18, particularly by researchers from the Fraunhofer ICT in Germany, and 1,4‐bis(1‐hydroxypropargyl)benzene (BHPB) by researchers from the Agency for Defense Development (ADD) in the Republic of Korea 10. Lately, other alkyne curing agents such as 2,2‐bis(prop‐2‐ynyl)malonate (DDPM) have been investigated by Chinese researchers 17.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of polyfunctional alkynes as alternative, isocyanate‐free curing agents for GAP binder systems is by now well‐established, at least at the laboratory scale 4–8, 10, 13, 14, 1618. Although a variety of such agents have been developed, the most comprehensibly explored ones have been bispropargyl succinate (BPS) 4–8, 14, 18, particularly by researchers from the Fraunhofer ICT in Germany, and 1,4‐bis(1‐hydroxypropargyl)benzene (BHPB) by researchers from the Agency for Defense Development (ADD) in the Republic of Korea 10. Lately, other alkyne curing agents such as 2,2‐bis(prop‐2‐ynyl)malonate (DDPM) have been investigated by Chinese researchers 17.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of nearly continuous developmental work taking place since the 1970s, certain aspects of the application of GAP binders, specifically those concerning mechanical characteristics, remain problematic. Research focused on GAP binder systems and associated fillers is currently in rapid progress, especially since about 2008 4–8, 1018. Particularly, the use of polyfunctional alkynes for isocyanate‐free curing of GAP under triazole formation is prevalent 4–8, 10, 13, 14, 1618.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the side reaction occurs between urethane and nitrate‐ester plasticizer . With the concept of “green propellants” , the ammonium dinitramide as new oxidizer is proposed to be used in propellants but it has poor compatibility with isocyanates .…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing gradient of ADN/AP system was much lower than the other four systems, and the value was decreasing a little but it still remained above 0.9 when AP was totally replaced by ADN. It indicated that as one of the most promising oxidants to replace AP [27][28][29][30], ADN was more effective to improve the oxygen content for low signature propellants.…”
mentioning
confidence: 99%